Synthesis and Antitumor Activity of a GSH Inert Bisphosphonate Platinum (II) Complex - Lu Ma; Hua Liu; Yichun Ju; Kai Chen; Yi Yang; Zhichao Zhou; Zhenqin Zhang; Zheng Cai (Journal of Chemistry)
Osteosarcoma is a highly aggressive neoplasm. Traditional platinum chemotherapeutic agents for osteosarcoma inevitably have acquired drug resistance and serious side effects, which have limited their utility. To slow down the reaction of platinum drugs with glutathione (GSH) is a strategy to overcome the resistance of platinum chemotherapeutic agents. Herein, the unique design of a GSH inert bisphosphonate platinum complex cis-{di(amino)platinum[tetraethyl 2,2-bis(2-pyridinylmethyl)methylidene-1,1-bisphosphonate]} (DBPP) is reported. MTT assay demonstrates that DBPP showed moderate inhibition towards human osteosarcoma cell line U2OS cells. The cytostatic action of DBPP is related to conformational conversion from B-DNA to A-DNA and the unwinding of pUC19 DNA. DBPP could also destroy the tertiary structure of human serum albumin (HSA). Notably, 31P NMR and 1H NMR indicate that DBPP can hardly chelate with GSH, which could overcome the GSH-induced side effects. We envision that this unique design of the platinum complex would open up new ways to overcome GSH-induced resistance.